2022
DOI: 10.1051/0004-6361/202142039
|View full text |Cite
|
Sign up to set email alerts
|

The SEDIGISM survey: A search for molecular outflows

Abstract: Context. The formation processes of massive stars are still unclear but a picture is emerging involving accretion disks and molecular outflows in what appears to be a scaled-up version of low-mass star formation. A census of outflow activity towards high-mass star-forming clumps in various evolutionary stages has the potential to shed light on high-mass star formation. Aims. We conducted an outflow survey towards ATLASGAL (APEX Telescope Large Area Survey of the Galaxy) clumps, using SEDIGISM (structure, Excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 95 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…They also suggested the possibility of the presence of small-scale outflows toward S1. Most recently, Yang et al (2022) examined the presence and absence of the 13 CO outflows toward the ATLASGAL clumps using the SEDIGISM 13 CO(J = 2-1) and C 18 O(J = 2-1) line data. One can find the detailed steps for identifying the outflows toward ATLASGAL clumps in Yang et al (2022).…”
Section: Distribution Of Molecular Gas In G33373mentioning
confidence: 99%
See 2 more Smart Citations
“…They also suggested the possibility of the presence of small-scale outflows toward S1. Most recently, Yang et al (2022) examined the presence and absence of the 13 CO outflows toward the ATLASGAL clumps using the SEDIGISM 13 CO(J = 2-1) and C 18 O(J = 2-1) line data. One can find the detailed steps for identifying the outflows toward ATLASGAL clumps in Yang et al (2022).…”
Section: Distribution Of Molecular Gas In G33373mentioning
confidence: 99%
“…Most recently, Yang et al (2022) examined the presence and absence of the 13 CO outflows toward the ATLASGAL clumps using the SEDIGISM 13 CO(J = 2-1) and C 18 O(J = 2-1) line data. One can find the detailed steps for identifying the outflows toward ATLASGAL clumps in Yang et al (2022). In our selected target area, six ATLASGAL clumps are traced (see Figure 1c), and the molecular outflow is reported toward only one ATLASGAL clump (i.e., AGAL333.724+00.364) hosting S1 (Yang et al 2022).…”
Section: Distribution Of Molecular Gas In G33373mentioning
confidence: 99%
See 1 more Smart Citation
“…We have cross-matched the ATLASGAL sample with four other star formation tracers to test the validity of the evolutionary sequence identified in this paper. We have used the catalogue of ∼300 extended green objects (EGOs; Cyganowski et al 2008), catalogues of molecular outflows produced by Maud et al (2015); de Villiers et al ( 2014); Yang et al (2018Yang et al ( , 2021, the methanol multibeam (MMB) survey (Green et al 2009) and water masers identified by HOPS (Walsh et al 2011(Walsh et al , 2014. EGOs are identified by their enhanced emission in the 4.5-µm band that contains the rotationally excited H 2 (v = 0 − 0, S(9, 10, 11)) and CO (v = 1 − 0) band-head lines, which are indicative of outflow activity and active accretion (Cyganowski et al 2008).…”
Section: Correlation With Other Samplesmentioning
confidence: 99%
“…Molecular clouds (see Heyer & Dame 2015 for a review) are usually observed in three-dimensional position-position-velocity (PPV) space or two-dimensional dust continuum emission (e.g., Bot et al 2007;Könyves et al 2015;Arzoumanian et al 2019). PPV data provide valuable information about properties of molecular clouds and activities in them, such as densities (e.g., Kauffmann et al 2017;Evans et al 2021), temperatures (e.g., Wang et al 2019;Mazumdar et al 2021), and molecular outflows (e.g., Snell et al 1980;Zhang et al 2001Zhang et al , 2020Yang et al 2018Yang et al , 2022, as well as large-scale structures of the Milky Way (e.g., Dame et al 2001;Sun et al 2015;Du et al 2017). Missing one dimension of position, PPV data are incomplete compared with position-position-position (PPP) data and are unable to distinguish molecular clouds in crowded regions, such as the first Galactic quadrant, and velocity degenerated directions, such as the Galactic anticenter.…”
Section: Introductionmentioning
confidence: 99%